2021
DOI: 10.3390/nu13092956
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Impact of Natural Sugars from Fruit Juices and Added Sugars on Caloric Intake, Body Weight, Glycaemia, Oxidative Stress and Glycation in Diabetic Rats

Abstract: Although fruit juices are a natural source of sugars, there is a controversy whether their sugar content has similar harmful effects as beverages’ added-sugars. We aimed to study the role of fruit juice sugars in inducing overweight, hyperglycaemia, glycation and oxidative stress in normal and diabetic animal models. In diabetic Goto-Kakizaki (GK) rats, we compared the effects of four different fruit juices (4-weeks) with sugary solutions having a similar sugar profile and concentration. In vitro, the sugary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…While their vascular function is apparently impaired from an early age, other tissues are apparently more conserved over time. These results are in accordance with the previous observations from our group [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…While their vascular function is apparently impaired from an early age, other tissues are apparently more conserved over time. These results are in accordance with the previous observations from our group [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is worth mentioning the difference between naturally occurring carbohydrates in foods and added sugars. Monteiro-Alfredo et al (2021) observed that sugars naturally present in fruit juices and added sugars have distinct effects in diabetic animal models, with harmful effects of added sugars. A high intake of added sugars increases the risk of weight gain and several chronic diseases, such as diabetes and cardiovascular disease and should, therefore, be avoided (Steele et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Among the chronic illnesses that have been progressively more common lately, we highlight obesity, which is usually caused by unhealthy lifestyle habits-such as the consumption of processed foods rich in long-chain saturated fatty acids and added sugars [5], a sedentary lifestyle, and overweight [6]-and affects the overall quality of life of the population, both physically and economically, as well as psychologically [7]. Obesity is considered a major public health problem and is ranked as the fifth leading cause of mortality worldwide [8].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is considered a major public health problem and is ranked as the fifth leading cause of mortality worldwide [8]. In addition to potentially leading to death, it can contribute to the development of other chronic disorders, including cancer [9], respiratory, hepatic, renal, and cardiovascular diseases (CVD) [10,11], and other metabolic disorders such as metabolic syndrome [8] and type 2 diabetes (T2D) [5,12].…”
Section: Introductionmentioning
confidence: 99%